Mirror - Baker, Jeannie (Somerville, Mass. : Candlewick Press, 2010)
In Sydney, Australia, and in Morocco, two boys and their families have a day of shopping. Readers are invited to compare illustrations in two wordless stories that are intended to be read one from left to right and the other from right to left.
Socials
Global
Primary
Keywords: Markets -- Fiction; Stories without words; Australia -- Fiction; Morocco -- Fiction